Manipulating the Local Coordination and Electronic Structures for Efficient Electrocatalytic Oxygen Evolution - Wu, Zhi‐Peng; Zhang, Huabin; Zuo, Shouwei; Wang, Yan; Zhang, Song Lin; Zhang, Jing; Zang, Shuang‐Quan; Lou, Xiong Wen (David) (Advanced materials (Weinheim), 2021)
Non‐noble‐metal‐based nanomaterials can exhibit extraordinary electrocatalytic performance toward the oxygen evolution reaction (OER) by harnessing the structural evolution during catalysis and the synergistic effect between elements. However, the structure of active centers in bimetallic/multimetallic catalysts is under long‐time debate in the catalysis community. Here, an efficient bimetallic Ni–Fe selenide‐derived OER electrocatalyst is reported and the structure–activity correlation during the OER evolution studied. By combining experiments and theoretical calculations, a conceptual advance is provided, in that the local coordination structure distortion and disordering of active sites inherited from the pre‐catalyst and post‐formed by a further reconstruction are responsible for boosting the OER performance. The active center is identified on Ni sites showing moderate bindings with oxygenous intermediates rather than Fe sites with strong and poisonous adsorptions. These findings provide crucial understanding in manipulating the local coordination and electronic structures toward rational design and fabrication of efficient OER electrocatalysts. Bimetallic Ni–Fe selenide‐derived (oxy)hydroxide nanocage electrocatalysts are in situ generated by inheriting the structure of the pre‐catalyst. The successful manipulation of the local coordination and electronic structures of the electrocatalyst enables superior electrocatalytic activity and stability for the oxygen evolution reaction.